Arsenic-induced apoptosis in the p53-proficient and p53-deficient cells through differential modulation of NFκB pathway - Yin, Lei (Food Chem Toxicol, 2018)
Arsenic is a well-known environmental carcinogen and an effective chemotherapeutic agent. The underlying mechanism of this dual-effect, however, is not fully understood. In this study, we applied mouse p53(+/+) and p53(−/−) cells to examine the NFκB pathway and proinflammatory cytokines after arsenic treatment. Arsenic reduced cell viability and increased more apoptosis in the p53−/− cells as compared to p53+/+ cells, which was correlated with activation of SAPK/JNK, p38 MAPK, and AKT pathways. A transcriptional regulatory network analysis revealed that arsenic activated transcription regulatory elements E2F, Egr1, Trp53, Stat6, Bcl6, Creb2 and ATF4 in the p53+/+ cells, while in the p53−/− cells, arsenic treatment altered transcription factors NFκB, Pparg, Creb2, ATF4, and Egr1. We observed dynamic changes in phosphorylated NFκB p65 (p-NFκB p65) and phosphorylated IKKαβ ( p-IKKαβ) in both genotypes from 4h to 24h after treatment, significant decreases of p-NFκB p65 and p-IKKαβ in the p53−/− cells, whereas increases of p-NFκB p65 and p-IKKαβ were observed in the p53+/+ cells. Our study confirmed the differential modulation of NFκB pathway by arsenic in the p53+/+ or p53−/− cells and this observation of the differential mechanism of cell death between the p53+/+ and p53−/− cells might be linked to the unique ability of arsenic to act as both a carcinogen and a chemotherapeutic agent.